Challenges to Privacy Protection on YouTube - Stepanović, Ivana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
Functioning as both a media platform, a social media platform and a new public space, YouTube allows instant sharing, but also multiplying and re-uploading the same content by different users, which makes videos virtually indestructible. Children and minors are especially vulnerable, either because they are too young to be asked for consent to appear in their parents’ videos or because they are not yet able to decide for themselves which private information can be made public. Laws in Serbia are failing to protect privacy on YouTube, which leaves individuals at the mercy of YouTube’s own privacy policies. The aim of this paper is to investigate new challenges to privacy protection by analysing its own policies, Serbian law and content uploaded by users. The goal is also to help raise awareness of this problem and stress the importance of educating children on digital privacy.